205k views
1 vote
Solve for x. 3(x-2) = -4x + 36

Solve for x. 3(x-2) = -4x + 36-example-1

1 Answer

4 votes

Answer:

x=6

Explanation:

Let's solve your equation step-by-step.

3(x−2)=−4x+36

Step 1: Simplify both sides of the equation.

3(x−2)=−4x+36

(3)(x)+(3)(−2)=−4x+36(Distribute)

3x+−6=−4x+36

3x−6=−4x+36

Step 2: Add 4x to both sides.

3x−6+4x=−4x+36+4x

7x−6=36

Step 3: Add 6 to both sides.

7x−6+6=36+6

7x=42

Step 4: Divide both sides by 7.

7x

7

=

42

7

x=6

User Kdt
by
4.8k points